2002
DOI: 10.1155/2002/202961
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits ofHelicobacter pyloriEradication: Current Status

Abstract: In patients with diseases known to be associated withHelicobacter pyloriinfection, such as peptic ulcer, treatment of the underlying infection is the standard of care. However, in most major consensus management guidelines, including those published in Canada, widespread testing forH pyloriinfection is not recommended. This practice is not encouraged because of insufficient evidence of cost-benefit in gastric cancer prevention, the potential for increases in antibiotic resistance and the controversial hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…34 Unfortunately, the extent to which H. pylori eradication decreases the risk of GC is unknown because of the lack of randomized controlled studies in large populations, raising a question as to whether population-based H. pylori screening and treatment should be undertaken. [35][36][37] Even the evidence supporting the eradication of H. pylori in fi rst-degree relatives of GC patients is uncertain according to the Maastricht 2-2000 Consensus Report. 38 The fi ndings of the present study indicate that H. pylori and host genotyping can be a useful tool for identifying high-risk individuals among dyspeptic patients and preferentially targeting them for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…34 Unfortunately, the extent to which H. pylori eradication decreases the risk of GC is unknown because of the lack of randomized controlled studies in large populations, raising a question as to whether population-based H. pylori screening and treatment should be undertaken. [35][36][37] Even the evidence supporting the eradication of H. pylori in fi rst-degree relatives of GC patients is uncertain according to the Maastricht 2-2000 Consensus Report. 38 The fi ndings of the present study indicate that H. pylori and host genotyping can be a useful tool for identifying high-risk individuals among dyspeptic patients and preferentially targeting them for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Many preventive measures can be implemented that can decrease the incidence of gastric cancer including screening, modification of diet and lifestyle and eradication of H. pylori . The feasibility of these strategies needs to be further studied especially the eradication of H. pylori in large populations as well as in familial high‐risk groups 6,7,8–13 . A program for the control of gastric cancer has been initiated in China and in collaboration with investigators around the world and the International Digestive Cancer Alliance 14 .…”
Section: Resultsmentioning
confidence: 99%
“…It is thus possible that dietary factors such as food temperature and salt concentration play an important part in atrophy lesion. It has also been reported that eradication of H. pylori cannot decrease the rate of incidence of gastric atrophic lesion,although abolishing or alleviating some symptom [49,50]. Therefore, H. pylori is an important but not the sole factor associated with atrophy lesion and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%